Optimization of phycobiliprotein biosynthesis in thermotolerant cyanobacteria through light parameter adjustment (2024)
This study addressed the optimization of biomass and C-phycocyanin (C-PC) concentration and its purity in the thermotolerant cyanobacterium Potamosiphon sp by adjusting key light quality parameters. Custom design and Central Composite Design experimental designs were employed, using LEDs light intensity, wavelength, and photoperiod. The results demonstrated that these lighting parameters significantly influence biomass and Cphycocyanin production, achieving up to a 100 % increase in phycocyanin accumulation and biomass production and a 50 % improvement in purity index compared to conventional white light under optimal conditions of Red: Blue light (3:1), Intensity (283 μmol m− 2 s− 1 ), and photoperiod (17.8 H light). The findings support the use of specific LEDs wavelengths that optimize the performance of production processes and the quality of products derived from cyanobacteria, such as high-value phycobiliproteins.